2012
DOI: 10.5152/jtgga.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial spiral artery Doppler parameters in unexplained infertility patients: is endometrial perfusion an important factor in the etiopathogenesis?

Abstract: Objective: Uterine perfusion, particularly the endometrial blood flow, may have an important role in endometrial receptivity. In order to assess the contribution of sub endometrial blood flow in the etiopathogenesis of unexplained infertility mid luteal-peri-implantation period spiral artery transvaginal color Doppler parameters were measured and compared with fertile controls. Material and Methods: Forty-two consecutive patients admitted toIzmir Katip Celebi University Ataturk Training and Research Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
(20 reference statements)
1
22
0
1
Order By: Relevance
“…The study affirms [5,2] that the E thickness and its structure, as well as its adequate vascularization are useful prognostic factors in relation to ET success in IVF cycles. The data on the minimal E thickness for a successful pregnancy vary in the literature.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The study affirms [5,2] that the E thickness and its structure, as well as its adequate vascularization are useful prognostic factors in relation to ET success in IVF cycles. The data on the minimal E thickness for a successful pregnancy vary in the literature.…”
Section: Discussionsupporting
confidence: 75%
“…), and the birthrate has not changed significantly [1]. Infertility prevalence is between 10 and 15% in the general population [2,3]. Its treatment by IVF is becoming increasingly popular in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Battaglia et al 39 reported the highest pregnancy rate in the group with lower resistance to blood flow in the uterine spi¬ral arteries. This finding revealing that the decrease in peripheral impedance in the uterine vasculature was considered to be a consequence of increased blood flow and a sign of high tissue perfusion, and this might be an important prerequisite for successful invitro fertilization and embryo transfer cycle (40) . With endometrial thickness less than 8 mm and no-tripleline pattern on hCG day in IVF/ICSI cycles, and high RI there is a poor chance of achieving pregnancy.…”
Section: Such Finding Coincided With Silverberg Et Almentioning
confidence: 88%
“…The endometrial blood flow as shown by the spiral artery may have an important role in endometrial receptivity. Accordingly, in a study, both pulsatility and resistance indexes of the spiral artery were found to be significantly higher in the infertile study group than in the fertile control group (12). Also, the spiral artery S/D ratio was lower in the patients who had a pregnancy compared to those who did not …”
Section: Behçet's Disease Patients' Disease Featuresmentioning
confidence: 91%